Agricultural contracts, adverse selection, and multiple inputs - Rachael Goodhue; Leo Simon (Agricultural and Food Economics, 2016)
A significant and growing share of US agricultural output is produced under a production or marketing contract. An important controversy regarding agricultural production contracts is the control of non-labor inputs. Over time, contracts have tended to place more inputs under the buyer's control and fewer under the farmer's. This analysis examines the welfare effects of this trend. In the framework considered here, returns are reduced for some farmers and left unaffected for others. Returns to the buyer increase. The net effect on total surplus has two components. Output is higher when the buyer controls the input, due to lower information rents accruing to more productive farmers. However, this reduction distorts input use away from the production cost-minimizing level, which is costly. The net effect on total surplus depends primarily on the elasticity of substitution between inputs. Given the limited substitutability between labor and non-labor inputs in many agricultural activities, the analysis suggests that greater control of non-labor inputs by the buyer increases total surplus. The increase in returns to the buyer is consistent with the growing share of output produced under vertical coordination and the tendency to specify a greater number of production activities rather than allowing farmers to make their own decisions. The reduction in the returns obtained by some farmers is consistent with farmers' opposition to such requirements.
Keywords: 330; Adverse selection; Agricultural contracts; Asymmetric information; Principal-agent theory; Production contracts; Vertical coordination